2014
DOI: 10.1183/09031936.00188013
|View full text |Cite
|
Sign up to set email alerts
|

Iloprost reverses established fibrosis in experimental right ventricular failure

Abstract: Prostacyclin and its analogues improve cardiac output and functional capacity in patients with pulmonary arterial hypertension (PAH); however, the underlying mechanism is not fully understood. We hypothesised that prostanoids have load-independent beneficial effects on the right ventricle (RV).Angio-obliterative PAH and RV failure were induced in rats with a single injection of SU5416 followed by 4 weeks of exposure to hypoxia. Upon confirmation of RV dysfunction and PAH, rats were randomised to 0.1 μg·kg −1 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
70
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 54 publications
(86 reference statements)
10
70
1
Order By: Relevance
“…Second, while we demonstrate favorable effects of endogenous or exogenous E 2 on proapoptotic signaling, eNOS phosphorylation, and autophagic flux, these parameters were not significantly affected by SuHx or sex. While this may suggest that these pathways do not play a role in RV failure, this is unlikely in light of previously published data that demonstrate pathophysiological relevance (6,14,29,46,47,52). A more likely explanation is that the present studies were underpowered to detect more profound changes in these endpoints.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Second, while we demonstrate favorable effects of endogenous or exogenous E 2 on proapoptotic signaling, eNOS phosphorylation, and autophagic flux, these parameters were not significantly affected by SuHx or sex. While this may suggest that these pathways do not play a role in RV failure, this is unlikely in light of previously published data that demonstrate pathophysiological relevance (6,14,29,46,47,52). A more likely explanation is that the present studies were underpowered to detect more profound changes in these endpoints.…”
Section: Discussioncontrasting
confidence: 41%
“…Since our correlation analyses linked impaired autophagic flux to worsening RV function and remodeling, these data suggest that improved autophagic flux may, at least in part, be a mechanism of how E 2 mediates RV-protective effects after acute exercise. Along these lines, stimulatory effects on autophagy have recently been suggested as a mediator of RV-protective and anti-fibrotic effects of the prostacyclin ilopprost (14). Taken together, these data suggest that autophagy may be a potentially important modifier of RV function in PAH.…”
Section: Discussionmentioning
confidence: 51%
“…44 Prostacyclin is able to reduce TNF-α-induced expression of VCAM1 in endothelial cells, 45 which is in accordance with the present results showing decreased VCAM1 expression after the epoprostenol infusion. Moreover, a recent study showed that prostacyclin is able to reverse established RV fibrosis in an experimental model of RV failure by preventing collagen synthesis and by increasing collagen turnover, 46 which is probably linked to the effects of prostacyclin on inflammatory processes. However, because of the different timing of myocardial sampling and the difficulty of performing biopsies in such an acute experimental model, we cannot exclude (at least partly) some timing effects on the activation of inflammatory processes, even if RV failure on acute transient increased afterload has been shown to be persist at least 120 minutes after the restoration of loading conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pathologically activated autophagy has been associated with various fibrotic diseases (23)(24)(25)(26)(27)). An overexpression of the autophagy marker LC3 was observed in human samples from a number of patients with OSF.…”
Section: Discussionmentioning
confidence: 99%